Banjarese College Students’ Positive Politeness toward Their Lecturers Through Online Chats - Menik Winiharti; Ahmad Mubarok (Lingua Cultura, 2023)
The research aimed to describe the positive politeness strategy which was applied by undergraduate students toward their lecturers in online conversations. It was also to find the form of violations of politeness that occurred in the conversation and to describe factors that influenced the violation. Data were gathered from online conversations between students and lecturers through chat applications such as WhatsApp and Line on lecturers' and students’ devices. Then the data were grouped and analyzed according to Brown and Levinson's (1987) positive politeness strategy along with their theory on Distance, Power, and Ranking of Imposition. The results show that positive politeness strategies appear in eleven utterances out of forty-three utterances. The violation of politeness is shown in five utterances, all of which threaten the negative face of the addressee. In addition, five factors influence the violation: distance, context, desire to over-praise the addressee, deliberately asking for reasons, and rejection. Overall, social factors still influence the way students communicate online with their lecturers. To some extent, students apply positive politeness strategies toward their lecturers even though the interaction happens through online chat applications.